Scandinavian Information Systems Research First Scandinavian Conference on Information Systems, SCIS 2010, Rebild, Denmark, August 20-22, 2010, Proceedings - Kautz, Karlheinz; Nielsen, Peter Axel (Lecture Notes in Business Information Processing, 2010)
The First Scandinavian Conference on Information Systems (SCIS 2010) took place during August 20-22, 2010 in Rebild, Denmark. The conference was held in conjunction with the traditional IRIS seminar for information systems research in Scandinavia. The IRIS seminar has a long-standing recognition for furthering information systems research. The objective of SCIS 2010 was to extend and formalize a part of the seminar to a full conference. The purpose of the conference was to exchange and publish high-quality research with a particular view on the Scandinavian research community. The theme of the conference was "Engaged Scandinavian Information Systems Research." Scandinavian information systems research has for several decades been concerned with its relevance for practitioners of the field, for users, for industry, and for society at large. This concern for the usefulness outside the realms of research has shaped the Scandinavian researchers' awareness, attention, research conduct, and most importantly a focus on who we interact with on which issues, why we do this, and for whom we do it.